Burnout Syndrome: A socio-clinical analysis among university students enrolled in health-related courses in the municipality of Cruzeiro do Sul, State of Acre (AC) (Research, Society and Development, 2025)
The Burnout Syndrome is a chronic stress emotional disorder related to the workplace or study environment. It is characterized by a symptomatic triad: emotional exhaustion, depersonalization, and reduced personal accomplishment. This study aimed to evaluate the perception about the Burnout Syndrome and investigate the intensity and risk of its occurrence among students in health-related courses in the municipality of Cruzeiro do Sul – AC. The research used an online survey (Google Forms), between March and April 2025. Among the 153 students participating in the research, 83% are medical students, aged between 18 and 46 years, with 58.8% being male and 41.2% female. The students are enrolled between the 1st and 9th semesters, with 23,5% in the 7th semester. The average income is R$1,000, and 63.4% of the students are not scholarship holders, and 68,6%  are financially and residentially dependent on their parents. Regarding the perception about the Burnout Syndrome, 86.2% recognize its etiology, and 92.8% are also aware of its manifestations. Concerning prevention, 60.2% identify the importance of professional support in face of the Burnout Syndrome. According to the Copenhagen Burnout Inventory scale, the majority of participants were classified with a low level of burnout (81.7%). In this sense, there is a need for attention towards the university students´ mental health, through welcoming actions and Burnout prevention strategies, thus contributing to well-being in the academic setting and professional development.